Parvirus infection markers in persons with exantemic diseases and in risk groups - I. N. Lavrentieva; A. Yu. Antipova; M. A. Bichurina; I. V. Khamitova; O. N. Nikishov; A. A. Kuzin (Журнал инфектологии)
Background. In the Russian Federation the number of a parvovirus В19 infection cases has increased significantly with the introduction of rubella into the measles elimination program and laboratory examination of patients with maculopapular rash and fever. The aim of study was the examination of the distribution of the parvovirus В19 infection in the North-Western Federal District. Materials and methods. In 2014–2017, 1044 blood sera of patients with exanthema diseases from different territories of the North-Western Federal District have been investigated with «Anti-Parvovirus B19 ELISA IgM» kit (EUROIMMUN, Germany) to detect IgM antibody, and 733 blood sera of clinically healthy men and women 18 to 60 years old have been tested for IgG antibodies using the «Anti-Parvovirus B19 ELISA IgG» kit (EUROIMMUN, Germany). Results. Parvovirus В19 infection is contentiously detected in 10 of the 11 territories of the district. Typical is the winterspring seasonality; in terms of the age structure – prevalence of children 3–6 (25,3% of cases) and 7–14 (33,3% of cases) years old was detected. A high proportion of seropositivity was established among the examined donors from the higher educational institutions of Saint Petersburg (75,4–88,9%%). Low rate of seropositivity (56,7%) was detected among pregnant women. A high proportion of false negative results in the primary diagnosis of parvovirus infection has been revealed. Conclusion. Parvovirus В19 infection is widespread in the territories of the North-Western of the Russia, mainly among children. The results indicate the feasibility of conducting a laboratory examination of pregnant women who are contact for exanthemous diseases, for markers of parvovirus infection; on the importance of screening donor blood for PV B19 DNA with “culling” pools characterized by high viral load; on the need for differential laboratory diagnosis between rubella and parvovirus infection.